Yttrium aluminum garnet powder and synthesis method thereof
By mixing yttrium oxide and silica powder, and using ball milling, spray drying, compacting, calcining and grinding, the problems of high cost, low yield and impurity levels in the prior art are solved, and high sintering and low cost YAG powder production are achieved.
Patent Information
- Application Number
- CN202280012217.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-29
- Filing Date
- 2022-01-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-01-28
AI Technical Summary
The prior art has problems of high cost, low yield and impurity levels in the production of yttrium aluminum garnet (YAG) powder, and requires high temperature and long-term sintering process, resulting in inefficiency.
Using mixed yttrium oxide powder and silica powder, YAG powder with controlled dopant concentration is formed by ball milling, spray drying, compacting, calcining and grinding, to avoid adding alumina, and the powder slurry is compacted before calcination to promote the transformation of the YAG phase.
High sintering and low cost YAG powder production is achieved, reducing calcining temperature and time, improving yield, and controlling the levels of dopants and impurities, producing high purity and high density YAG powder.
Smart Images

Figure CN116897143B_ABST
Abstract
Description
[0001] priority
[0002] This application is related to and claims priority to U.S. Provisional Patent Application No. 63 / 143,605, filed on January 29, 2021, which is incorporated herein by reference. Technical Field
[0003] The present disclosure relates to the synthesis of yttrium aluminum garnet (YAG) powders and processing methods for providing YAG powders with controlled dopant concentrations. Background Art
[0004] Yttrium aluminum garnet (YAG, yttrium aluminate, Y 3 Al 5 O 12 ) or YAG doped with appropriate ions has been widely used in various applications, such as phosphors in solid-state lasers and projectors, solid-state lighting, head-up displays, professional lighting, cathode ray tubes, light-emitting diodes, scintillators, etc.
[0005] Conventional methods for making YAG powders include, as example pathways, chemical coprecipitation, mixed precipitation, glycine-nitrate, citrate, dissolving yttrium oxide in alumina sol, amorphous foam, inductively coupled thermal plasma synthesis, hydrothermal, nanopowder processing, microwave coupling, etc. However, the resulting powders produced by the above techniques are expensive, time-consuming to manufacture, require small batch sizes, and may also have environmental disadvantages associated with the process. In addition, the resulting impurity levels may be lower than the levels required for certain applications. This places considerable and unnecessary demands on resources.
[0006] While a variety of methods for making YAG powders are available, there remains a need for a simple solid-state powder synthesis method that improves yield and controls the levels of dopants, second or minor phases, and / or impurities while also providing sinterability at lower temperatures than conventional solid-state synthesized powders. Summary of the invention
[0007] In one embodiment, the present disclosure relates to a method for synthesizing yttrium aluminum garnet (YAG) powder. The method includes mixing yttrium oxide powder and silicon dioxide powder to form a powder mixture. The powder mixture does not contain aluminum oxide. The powder mixture may contain a dopant. The method may also include ball milling, spray drying, compacting, calcining and grinding to form YAG powder. The powder mixture may be ball milled in the presence of aluminum oxide grinding media and a solvent to form a powder slurry. Spray drying the powder slurry may form a spray-dried powder. The spray-dried powder may be compacted to a theoretical density of 35% or less to form a green compact. The green compact may be calcined in air to a theoretical density of 50% or less to form a YAG compact. Grinding the YAG compact without a grinding medium and then drying may produce a YAG powder. The yttrium oxide powder may have a purity of 2N or more, or a purity of 3N or more. Based on the total weight of the powder mixture, the content of silicon dioxide may be 0.1 wt % to 0.3 wt %. The silicon dioxide may be fumed silicon dioxide. Alumina grinding media can have a purity of 95.0% to 99.8% Al 2 O 3 .
[0008] Mixing to form a powder mixture can also include a dopant, which includes a lanthanide or a transition metal. The lanthanide or transition metal can be in the form of a compound, wherein the compound is an oxide, a hydrate, a nitrate, a chloride or a combination thereof. The lanthanide or transition metal is ionized to +3 and can have an ionic radius equal to or less than 0.114nm. The lanthanide or transition metal can include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium or a combination thereof. The lanthanide or transition metal can be scandium, zinc or cerium. Based on the gross weight of the powder mixture, a dopant of 10ppm to 6% by weight can be included. Based on the gross weight of the powder mixture, the dopant can be 0.1% by weight to 5% by weight of cerium dioxide. The dopant may be less than 3 wt% ceria based on the total weight of the powder mixture. The dopant compound may be ceria (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 7H 2 O) or cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O).
[0009] Ball milling the powder slurry can include loading the powder mixture, solvent and alumina grinding media into a ball mill container with a polymer liner. The solvent can be distilled water or deionized water (ethanol and isopropanol). Before spray drying the powder slurry, an organic binder can be added to the powder slurry. The organic binder can be water-soluble. Based on the total weight of the powder slurry, the content of the organic binder can be 3 wt % to 9 wt %. The composition after ball milling can include a stoichiometric amount of 3Y 2 O 3 :5Al 2 O 3 (0.6:1) and less than 3 wt% additional Al 2 O 3 . Additional Al 2 O 3 An eroded portion of the alumina abrasive media may be included.
[0010] Compacting the spray-dried powder may include uniaxial pressing or cold isostatic pressing. Compacting the spray-dried powder may be performed in air at room temperature. Compacting the spray-dried powder may be performed at a pressure of 500 psi to 1250 psi. Calcination may be performed at a temperature of 1100° C. to 1650° C. or 1450° C. to 1550° C. Calcination may be performed for 2 hours to 64 hours, or 8 hours to 16 hours. Grinding the YAG compact may include charging the compact and the solvent into a grinding container having a polymer liner. The solvent may be ethanol or isopropanol. Grinding the YAG compact may include grinding for at least 6 hours. Grinding the YAG compact may include causing the YAG compact material to self-comminute against itself to produce a YAG powder having an average particle size distribution of less than 100 μm. The average particle size distribution may be less than 63 μm, or less than 44 μm. The ground YAG compact material may be sieved before drying. The YAG powder may have a bimodal particle size distribution. Drying may be performed at a temperature below 90° C.
[0011] In some embodiments, a method for synthesizing doped yttrium aluminum garnet (YAG) powder includes providing yttrium oxide powder, silica powder, and at least one dopant powder formed of an oxide, hydrate, nitrate, or chloride of a lanthanide element or transition metal and mixing to form a powder mixture, wherein no alumina is added to the powder mixture. The method may further include: ball milling the powder mixture in the presence of an alumina grinding medium and a solvent to form a powder slurry, adding an organic binder to the powder slurry and mixing to form a sprayable powder slurry, and spray drying the sprayable powder slurry to form a spray-dried powder. The method may further include compacting the spray-dried powder to a theoretical density of 35% or less to form a green compact. The method may further include calcining the green compact in air to a theoretical density of 50% or less to form a YAG compact. The method may include a yttrium aluminum garnet compact having a YAG content of at least 92% by weight or more. 3 Al 5 O 12 The method may further include grinding the YAG compact without a grinding media and then drying to produce a doped YAG powder.
[0012] In some aspects, the yttrium aluminum garnet (YAG) composition comprises Y 3 Al 5 O 12 and less than 3 wt% additional Al 2 O 3 , where the additional Al 2 O 3 An eroded portion of an alumina grinding medium is included. The composition may also include a dopant concentration of at least 1 at%. An article, such as a phosphor wheel, may include a yttrium aluminum garnet (YAG) composition as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] A further understanding of the nature and advantages of the disclosed technology may be realized by reference to the remainder of the specification and drawings.
[0014] Figure 1 is a flow chart of an exemplary method;
[0015] Figure 2 is a graph showing the amount of alumina eroded as a function of charge weight ratio of alumina grinding media to yttria according to an exemplary method;
[0016] Figure 3 is an X-ray diffraction pattern of a ceria-doped YAG powder according to an exemplary method;
[0017] Figure 4is a scanning electron microscope (SEM) image of a cerium-doped YAG powder (e.g., after sintering at 1500° C. for 8 hours in air) according to an exemplary method;
[0018] Figure 5 is an X-ray diffraction pattern of undoped YAG powder after repeated calcination cycles according to an exemplary method;
[0019] Figure 6 are SEM images showing energy dispersive spectroscopy (EDS) analysis of a comparative cerium-doped YAG powder (eg, after sintering at 1600° C. for 8 hours in air) at different points. DETAILED DESCRIPTION
[0020] introduction
[0021] As described above, YAG powder produced using previous methods cannot meet the requirements of yield, cost and sinterability. Specifically, the previous solid-state method for manufacturing YAG powder requires repeated calcination at higher temperatures and for longer periods of time, and thus lacks processing efficiency, such as low product yield. In addition, in order to achieve high-density products, the previous solid-state method for manufacturing YAG powder requires a higher sintering temperature, such as a sintering temperature of 1600°C or higher.
[0022] The present inventors have now discovered that a simpler and more efficient production process can be achieved by using alumina grinding media in the first (ball) milling, compacting the resulting powder slurry prior to calcination, and using little or no grinding media in the final milling.
[0023] Without being bound by theory, it is speculated that the disclosed method promotes a more efficient transformation to the YAG phase during calcination and also prevents undesirable sources of impurities during each milling process. It has been found that controlling the alumina content by ball milling with alumina milling media results in a more efficient process, for example, a process that provides a stoichiometric or super-stoichiometric alumina content by milling, which enhances the transformation to the YAG phase and avoids the introduction of undesirable impurities. Compacting the powder slurry prior to calcination further enhances the transformation to the YAG phase, which can be advantageously performed at lower temperatures, shorter times, and / or with fewer calcination cycles, all of which contribute to a more efficient process, for example, a process with increased yields.
[0024] In addition, by not introducing any grinding media in the post-calcination grinding, the method provides higher purity and better control over the composition of the components, thereby producing a purer YAG powder, such as a YAG powder with fewer impurities. Without being bound by theory, it is believed that the combination of compaction before calcination and the introduction of alumina by grinding facilitates a more uniform distribution of alumina in yttrium oxide, which allows shorter time and / or lower temperature to complete the reaction between alumina and yttrium oxide, which in turn enhances the phase transition to YAG. Importantly, by employing the disclosed method, the dopant concentration can be advantageously controlled. As a result, the doped YAG contains fewer undesirable impurities.
[0025] Moreover, the disclosed method produces a YAG powder that performs better than conventional YAG powders. For example, the disclosed YAG powder exhibits high sinterability, for example, the YAG powder is sintered to a higher density at a relatively low sintering temperature compared to conventional solid-state synthetic powders. This is due to the use of low-temperature calcination, which is provided by adopting the above-mentioned grinding and compacting steps. Because the YAG phase transition is achieved at a relatively low calcination temperature, the disclosed YAG powder advantageously has fewer hard sintered blocks and a smaller average grain size. In contrast, conventional YAG powders are prepared at higher calcination temperatures, which disadvantageously produce harder sintered blocks, resulting in low sinterability. For example, in the subsequent sintering process, the disclosed YAG powder can reach a theoretical density of 98% when sintered at 1537°C for 8 hours, while a commercially available YAG powder (Intematix G91, Fremont CA) can only reach a theoretical density of 83% when sintered at 1537°C for 8 hours. Therefore, solid-state methods are needed to produce high-quality powders with controlled dopant concentrations, high sinterability, and lower manufacturing costs.
[0026] The disclosed method provides YAG suitable for a variety of applications, such as phosphor wheels, light emitting diodes (LEDs) (including white light emitting diodes (WLEDs)), optical lenses and NIR (near infrared) transparent windows for laser-based automotive engine igniters (e.g., as a replacement for spark plugs), lasers, laser guns, etc.
[0027] YAG powder synthesis method
[0028] The present disclosure relates to a method for synthesizing YAG powder having the above advantages. Figure 1An embodiment of the method is shown in . The method includes the steps of mixing powders of yttrium oxide and silicon dioxide to form a powder mixture and ball milling the powder mixture to form a powder slurry. Importantly, the ball milling is carried out in the presence of alumina grinding media and a solvent. This is important because it allows the amount of alumina in the powder slurry to be controlled, and even superstoichiometric amounts of alumina can be introduced if desired, without introducing unwanted impurities from traditional grinding media (such as grinding balls). In some cases, the powder mixture does not contain alumina (alumina is not added to the powder). The method further includes the steps of spray drying the powder slurry to form a spray-dried powder and compacting the spray-dried powder to a theoretical density of 35% or less to form a green compact. This advantageously allows the green compact to be more easily converted to the YAG phase during calcination than loose green material. The method further includes the steps of: calcining the green compact in air to a theoretical density of 50% or less to form a YAG compact; and grinding the YAG compact without grinding media and then drying to produce a YAG powder. Grinding the YAG compact in the absence of grinding media is important because it prevents the introduction of unwanted impurities from the grinding balls into the final powder composition. Each of these steps is discussed in more detail below.
[0029] As described above, use of the above methods, such as the compaction step, optionally in combination with ball milling (using aluminum grinding media), provides the above surprising results.
[0030] Original powder
[0031] As mentioned above and Figure 1 As exemplified in the method, the method comprises mixing a raw powder such as yttrium oxide (Y 2 O 3 ) powder and silicon dioxide (SiO 2 ) powder to form a powder mixture.
[0032] The raw powder used in the mixing step includes yttrium oxide and silicon dioxide. In some cases, the yttrium oxide powder is high-purity yttrium oxide. For example, the purity of the yttrium oxide powder can be greater than (and include) 2N (99%), such as 3N (99.9%) or 4N (99.99%). In some embodiments, the purity of the yttrium oxide powder is 3N. In some cases, the purity of the yttrium oxide powder is greater than (and include) 3N.
[0033] Silica and yttrium oxide can be mixed as separate powders, or the original powder can be, for example, yttrium oxide rich in silica. In this case, no mixing step is required, and silica / yttrium oxide powder can be provided directly. In a preferred embodiment, the silica is fumed silica. Fumed silica or pyrogenic silica has a low bulk density and a high surface area. These characteristics make fumed silica highly reactive in powder synthesis, especially during high temperatures for calcination. During calcination, silica reacts with yttrium oxide and alumina to form a Y-Al-Si-O liquid phase. This Y-Al-Si-O liquid phase evaporates at temperatures above 1350°C. A liquid phase is formed by adding silica, and a cleaning effect is achieved by evaporation of the Y-Al-Si-O liquid phase. The transient liquid phase removed by evaporation during calcination (or sintering) can be a cleaning agent. Suitable yttria powders and silica powders are commercially available, such as yttria (via Materion Corp.) and fumed silica (via Sigma-Aldrich).
[0034] In some embodiments, the powder mixture includes 0.005% to 2.0% by weight of silicon dioxide and the remainder of yttrium oxide. For example, the powder mixture can include 0.005% to 2.0% by weight of silicon dioxide, for example, 0.01% to 1.5% by weight of silicon dioxide, 0.01% to 1.0% by weight of silicon dioxide, 0.01% to 0.5% by weight of silicon dioxide, 0.05% to 0.4% by weight of silicon dioxide, 0.1% to 0.4% by weight of silicon dioxide, 0.1% to 0.3% by weight of silicon dioxide or 0.2% to 0.3% by weight of silicon dioxide. In terms of lower limits, the powder mixture can include greater than 0.005% by weight of silicon dioxide, for example, greater than 0.01% by weight, greater than 0.05% by weight, greater than 0.1% by weight or greater than 0.2% by weight. In terms of upper limits, the powder mixture may include less than 2.0 wt % silicon dioxide, e.g., less than 1.5 wt %, less than 1.0 wt %, less than 0.5 wt %, less than 0.4 wt % or less than 0.3 wt %. In some embodiments, the content of silicon dioxide is 0.1 wt % to 0.3 wt % based on the total weight of the powder mixture. Examples herein include silicon dioxide in an amount of 0.25 wt % based on the total weight of the powder mixture.
[0035] In some embodiments, the powder mixture comprises 93.0% to 99.99% by weight of yttrium oxide. The yttrium oxide content is the remainder in the powder mixture, which also depends on whether an optional dopant as described below is added. For example, the powder mixture can comprise 93.0% to 99.99% by weight of yttrium oxide, for example, 93.0% to 99.95% by weight of yttrium oxide, 95.0% to 99.9% by weight of yttrium oxide, 97.0% to 99.8% by weight of yttrium oxide, or from 98.0% to 99.8% by weight of yttrium oxide. With regard to the lower limit, the powder mixture can comprise greater than 93.0% by weight of yttrium oxide, for example, greater than 95.0% by weight, greater than 97.0% by weight, greater than 98.0% by weight, greater than 99.0% by weight, greater than 99.5% by weight, or greater than 99.9% by weight. In terms of upper limits, the powder mixture may contain less than 99.99% by weight of yttrium oxide, for example, less than 99.95% by weight, less than 99.9% by weight, less than 99.8% by weight, less than 99.5% by weight, or less than 99.0% by weight. In some embodiments, when no dopant is added, the content of yttrium oxide is 99.7% to 99.8% by weight based on the total weight of the powder mixture. In some embodiments, when a dopant is added, the content of yttrium oxide is 96.0% to 99.0% by weight based on the total weight of the powder mixture.
[0036] In some cases, the powder mixture contains little, if any, aluminum oxide (Al 2 O 3 In some embodiments, the powder mixture contains no or substantially no aluminum oxide (Al 2 O 3 ). In some cases, alumina is not added to the powder mixture. In some embodiments, the powder mixture comprises 0 wt% (0.00 wt%) to 0.5 wt% alumina. For example, the powder mixture may comprise 0.01 wt% to 0.5 wt% alumina, for example, 0.05 wt% to 0.4 wt% alumina, 0.1 wt% to 0.3 wt% alumina, or 0.1 wt% to 0.2 wt% alumina. In terms of upper limits, the powder mixture may comprise less than 0.5 wt% alumina, for example, less than 0.4 wt%, less than 0.3 wt% or less than 0.2 wt%. This is important because alumina can be removed from the method as a raw powder. It was found that by using alumina grinding media as the only alumina source introduced during ball milling, not only the method is simplified, but also alumina is evenly distributed in yttrium oxide, and the amount of alumina in the powder slurry during ball milling can be controlled.
[0037] Optionally, a dopant is included in the powder mixture. The dopant can be used in the form of a compound, and the dopant (dopant compound) can be added to and / or included in the powder mixture. In some embodiments, the powder mixture includes 10ppm to 6.0% by weight of a dopant and silicon dioxide as described above and the yttrium oxide of the remainder. For example, the powder mixture can include 10ppm to 6.0% by weight of a dopant, for example, 0.01% by weight to 6.0% by weight of a dopant, 0.5% by weight to 5.0% by weight of a dopant, 1.0% by weight to 4.0% by weight of a dopant, 1.5% by weight to 3.5% by weight of a dopant, 2.0% by weight to 3.0% by weight of a dopant, or 2.3% by weight to 2.7% by weight of a dopant. In terms of a lower limit, the powder mixture can include a dopant greater than 10ppm, for example, greater than 0.01% by weight, greater than 0.5% by weight, greater than 1.0% by weight, greater than 1.5% by weight, greater than 2.0% by weight, or greater than 2.3% by weight. In terms of upper limits, the powder mixture may contain less than 6.0 wt % of dopant, for example, less than 5.0 wt %, less than 4.0 wt %, less than 3.5 wt %, less than 3.0 wt % or less than 2.7 wt %. In a preferred embodiment, the content of dopant is 2.0 wt % to 3.0 wt % based on the total weight of the powder mixture.
[0038] In some embodiments, dopant is cerium added in the form of ceria. For example, powder mixture can include 0.1 wt % to 5.0 wt % ceria, for example, 0.5 wt % to 5.0 wt % ceria, 1.0 wt % to 4.0 wt % ceria, 1.5 wt % to 3.5 wt % ceria, 2.0 wt % to 3.0 wt % ceria, or 2.3 wt % to 2.7 wt % ceria. In terms of lower limit, powder mixture can include ceria greater than 0.1 wt %, for example, greater than 0.5 wt %, greater than 1.0 wt %, greater than 1.5 wt %, greater than 2.0 wt % or greater than 2.3 wt %. In terms of upper limit, powder mixture can include ceria less than 5.0 wt %, for example, less than 4.0 wt %, less than 3.5 wt %, less than 3.0 wt % or less than 2.7 wt %. In a preferred embodiment, the content of cerium dioxide is 2.5 wt%±10%, based on the total weight of the powder mixture.
[0039] The average particle size of the original powder is non-limiting. For example, the average particle size of the original powder can range from 0.001 μm to 50 μm, for example, 0.005 μm to 25 μm, 0.01 μm to 10 μm, or 0.01 μm to 5 μm. In terms of the lower limit, the average particle size of the original powder can be greater than 0.001 μm, for example, greater than 0.005 μm, or greater than 0.01 μm. In terms of the upper limit, the average particle size of the original powder can be less than 50 μm, for example, less than 25 μm, less than 10 μm, or less than 5 μm. The average particle size of the original powder is not a major factor in predicting, for example, the density of the green compact to be formed and / or the completeness of the phase transition to YAG after calcination. More importantly for providing a complete YAG phase transition in the method herein is compaction before calcination, which will be described in detail below.
[0040] One time grinding
[0041] As described above, the method includes the steps of ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry. As used herein, "ball milling" refers to a primary milling step of the method in which alumina is used as a grinding media. Using alumina in this manner is different from using conventional grinding balls that may not contain alumina. This step is important because the alumina content can be controlled, which results in providing a stoichiometric YAG or a super-stoichiometric alumina content as desired, which can enhance the phase transition to YAG.
[0042] Ball milling of the powder mixture can be carried out in the presence of alumina grinding media (and solvent) to form a powder slurry. The inventors have found that during ball milling, alumina is eroded from the grinding media to advantageously provide a source of alumina for the powder slurry. Advantageously, no additional alumina needs to be added or present.
[0043] Alumina grinding media is important because the amount of alumina eroded from the alumina grinding media can be advantageously controlled. Thus, the composition of the resulting YAG can also be controlled. This contributes to process efficiency and the aforementioned increases in production yields and / or shorter calcination cycles. Conventional YAG synthesis methods do not use alumina grinding media to intentionally erode alumina and / or deviate from stoichiometric YAG and therefore cannot achieve these benefits.
[0044] Factors that determine the amount of alumina provided to the powder slurry during ball milling include: grinding energy, milling speed revolutions per minute (RPM), diameter of the ball mill container, powder mixture loading in the powder slurry, volume of the powder slurry, volume and / or weight of the alumina grinding media, and the abrasive characteristics of the alumina grinding media. Factors may be interrelated, for example, the larger the diameter of the container, the slower the rotation. The peripheral speed of the mill is controlled to prevent the balls from being continuously passed through the container like a centrifuge, but instead staying at the periphery of the mill.
[0045] Y 2 O 3 (Yttrium Oxide) and Al 2 O 3 The molar nominal stoichiometric ratio of (aluminum oxide) is 3:5 or 3Y 2 O 3 :5Al 2 O 3 . In some cases, after ball milling, a superstoichiometric amount of aluminum oxide is present in the powder slurry. In other words, the ratio of yttrium oxide to aluminum oxide is greater than (or equal to) 3:5 (0.6:1), for example, 3:5.1 (0.59:1), 3:5.2 (0.58:1), 3:5.3 (0.57:1), 3:5.35 (0.56:1), 3:5.4 (0.555:1), 3:5.5 (0.55:1), 3:5.6 (0.54:1), 3:5.7 (0.53:1) or more. In some embodiments, the composition of the powder mixture after ball milling has a Y ratio of 3:5 (0.6:1) to 3:5.5 (0.55:1). 2 O 3 :Al 2 O 3 ratio.
[0046] After ball milling, the composition contains stoichiometric amounts of 3Y 2 O 3 :5Al 2 O 3 and less than 3 wt% additional Al based on the total weight of the powder composition 2 O 3 For example, additional Al 2 O 3 The amount may be from 0 (0.00) wt. % to 3.0 wt. % of additional Al 2 O 3 , for example, 0.1 wt % to 3.0 wt % additional Al 2 O 3 , 0.5 wt% to 2.5 wt% additional Al 2 O 3 , or 1.0 wt% to 2.0 wt% additional Al 2 O 3 As a lower limit, additional Al 2 O 3 The amount may be greater than 0 (0.00) wt. % additional Al 2 O 3 , for example greater than 0.1 wt% additional Al 2 O 3 , more than 0.5 wt% additional Al 2 O3 or more than 1.0 wt% additional Al 2 O 3 As far as the upper limit is concerned, the additional Al 2 O 3 The amount may be less than 3.0 wt% additional Al 2 O 3 , for example less than 2.5 wt% additional Al 2 O 3 , or less than 2.0 wt% additional Al 2 O 3 . Additional Al 2 O 3 This includes the erosion of the alumina grinding media. The erosion is due to the wear of the alumina grinding media during the ball milling process.
[0047] The aluminum oxide grinding media has a high purity. In some embodiments, the aluminum oxide grinding media has a purity of 95.0% to 99.99% Al 2 O 3 For example, the purity of aluminum oxide grinding media is 95.0% to 99.9% Al 2 O 3 , for example, 95.0% to 99.8% Al 2 O 3 , 97.0% to 99.8% Al 2 O 3 , 98.0% to 99.8% Al 2 O 3 , 99.0% to 99.8% Al 2 O 3 , or 99.5% to 99.8% Al 2 O 3 At the lower limit, the purity of the alumina grinding media is greater than 95.0% Al 2 O 3 , for example, greater than 95.0% Al 2 O 3 , greater than 96.0% Al 2 O 3 , more than 97.0% Al 2 O 3 , more than 98.0% Al 2 O 3 , more than 99.0% Al 2 O 3 , greater than 99.5% Al 2 O 3 , greater than 99.8% Al 2 O 3 or more than 99.9% Al 2 O3 On the upper limit, the purity of the alumina grinding media is less than 100% Al 2 O 3 , for example, less than 99.99% Al 2 O 3 , less than 99.9% Al 2 O 3 or less than 99.8% Al 2 O 3 In a preferred embodiment, the purity of the aluminum oxide grinding media is 95.0% to 99.8% Al 2 O 3 . High purity alumina grinding media is α-Al 2 O 3 The diameter of the alumina grinding media ranges from 3mm to 25mm. The alumina grinding media is wear-resistant, with a Vickers hardness of 14GPa (±10%) and a density of 3.88g / cm 3 Up to 3.97g / cm 3 The wear of alumina grinding media will cause the average particle size of Al2O3 to be distributed in the micrometer range. 2 O 3 The particles imparted to the powder mixture are, for example, 1 μm to 10 μm. In some aspects, Al 2 O 3 The particles are from 1 μm to 5 μm or from 1 μm to 3 μm. This is important because the transformation to the YAG phase can be enhanced during calcination by controlling the amount of alumina present and controlling the size of the alumina particles.
[0048] In some cases, ball milling is performed in a ball milling container with a polymer liner. The dimensions of the container can be 15 cm to 60 cm in diameter and 15 cm to 60 cm in height. Ball milling can be performed in a non-reactive container, such as a grinding jar with a polyurethane liner, for example, an Abbethane jar with a lift unit from Paul O'Abbe (Bensenville, IL), which has dimensions of: 30 cm diameter x 30 cm height. The contents of the polymer-lined ball milling container include a powder slurry containing a powder mixture, a solvent, and an alumina grinding media. The solvent can be distilled water or deionized water. The amount of the solvent is 50 wt % to 80 wt % based on the total weight of the powder mixture.
[0049] Ball milling can be performed at a speed of 15RPM to 70RPM. For example, the ball milling speed can be 15RPM to 70RPM, for example, 30RPM to 70RPM, or 50RPM to 70RPM. Ball milling can be performed for a time of 1 hour to 64 hours. For example, the ball milling time can be 1 hour to 64 hours, for example, 4 hours to 48 hours, 8 hours to 24 hours, or 12 hours to 20 hours. In some embodiments, ball milling is performed for 16 hours at 60RPM. The amount of aluminum oxide imparted to the powder slurry can be calculated by measuring the weight difference of the aluminum oxide grinding media relative to the initial weight of the aluminum oxide grinding media after ball milling. The grinding media can be cylindrical or spherical or other shapes with a diameter and / or height of about 13mm. For example, the grinding media can have a diameter of 10mm to 20mm and a height of 10mm to 20mm, for example, a diameter of 12mm to 18mm and a height of 12mm to 18mm, or a diameter of 13mm to 16mm and a height of 13mm to 16mm. The wear (erosion by weight) of the alumina grinding media can be 5 wt % to 10 wt %, e.g., 6 wt % to 8 wt %, or 6.5 wt % to 7 wt %.
[0050] Before spray drying the powder slurry, an organic binder may be added to the powder slurry. The organic binder is preferably water soluble. Suitable organic binders include ammonium solutions based on acrylic polymers (B-60A, commercially available from Rohm and Haas) or polyvinyl alcohol solutions, etc.
[0051] Based on the total weight of the powder slurry, the organic binder added before spray drying can be present in an amount of 3% to 9% by weight of the organic binder, for example, 4% to 8% by weight of the organic binder, 5% to 7% by weight of the organic binder, or 5.5% to 6.5% by weight of the organic binder. In terms of the lower limit, the amount of the organic binder added can be greater than 3% by weight of the organic binder, for example, greater than 4% by weight of the organic binder, greater than 5% by weight of the organic binder, or greater than 5.5% by weight of the organic binder. In terms of the upper limit, the amount of the organic binder added can be less than 9% by weight of the organic binder, for example, less than 8% by weight of the organic binder, less than 7% by weight of the organic binder, or less than 6.5% by weight of the organic binder. In a preferred embodiment, the amount of the organic binder added is 6% by weight ± 10% based on the total weight of the powder mixture. The organic binder is then burned out in a subsequent processing process, for example at 500° C. or higher, for example, during calcination.
[0052] Spray drying
[0053] The method may also include a step of spray drying the powder slurry to form a spray-dried powder. This step is important because spray drying forms discrete particles with uniform distribution of yttrium oxide, silicon dioxide, aluminum oxide, and optional dopants. Spray drying can be performed using a Yamato DL4120 (Santa Clara, CA) device. The inlet temperature may range from 200°C to 400°C, for example, from 200°C to 350°C, from 200°C to 300°C, from 200°C to 280°C, from 210°C to 270°C, from 220°C to 260°C, or from 230°C to 250°C. In terms of a lower limit, the inlet temperature may be greater than 200°C, for example, greater than 210°C, greater than 220°C, or greater than 230°C. In terms of an upper limit, the inlet temperature may be less than 400°C, for example, less than 350°C, less than 300°C, less than 280°C, less than 270°C, less than 260°C, or less than 250°C. In a preferred embodiment, the inlet temperature is 240°C ± 10%. The range of the outlet temperature can be 70°C to 110°C, for example, 75°C to 105°C, 80°C to 100°C or 85°C to 95°C. In terms of the lower limit, the outlet temperature can be greater than 70°C, for example, greater than 75°C, greater than 80°C or greater than 85°C. In terms of the upper limit, the outlet temperature can be less than 110°C, for example, less than 105°C, less than 100°C or less than 95°C. In a preferred embodiment, the outlet temperature is 85°C to 95°C. Spray drying is carried out under compressed air. The pressure of spray drying can be 0.01MPa to 0.6MPa of compressed air, for example, 0.02MPa to 0.5MPa, 0.05MPa to 0.4MPa or 0.1MPa to 0.3MPa. In terms of the lower limit, the pressure can be greater than 0.01MPa, for example, greater than 0.02MPa, greater than 0.05MPa or greater than 0.01MPa. In terms of the upper limit, the pressure can be less than 0.6MPa, for example, less than 0.5MPa, less than 0.4MPa or less than 0.3MPa. In a preferred embodiment, the pressure is 0.1MPa to 0.3MPa of compressed air.
[0054] The spray-dried powder includes an average particle size distribution ranging from 0.1 μm to 425 μm. The average particle size distribution can be in the range of 0.1 μm to 425 μm, such as 0.1 μm to 300 μm, 0.1 μm to 200 μm, 0.1 μm to 100 μm, 0.1 μm to 75 μm or 0.1 μm to 50 μm. In terms of the lower limit, the average particle size distribution can be greater than 0.1 μm, for example, greater than 0.2 μm, greater than 0.3 μm, greater than 0.4 μm or greater than 0.5 μm. In terms of the upper limit, the average particle size distribution can be less than 425 μm, for example, less than 300 μm, less than 200 μm, less than 100 μm, less than 75 μm or less than 50 μm. In an embodiment, the spray-dried powder can pass through a sieve (US40 mesh, 425 μm) so that any and all 425 μm particles can be used for compaction.
[0055] Compaction
[0056] The method further includes the step of compacting the spray-dried powder to form a green compact. Compared with the traditional powder solid-state calcination method that is not compacted in this way, the spray-dried powder is compacted to provide several method advantages. First, in the subsequent calcination process, the powder composition will be more easily converted into a YAG phase, because the green compact has a higher green density relative to the loose powder for calcination, so the ion diffusion distance required for forming the YAG phase is shorter. Therefore, the formation of YAG will be carried out at a lower calcination temperature and / or less time than the loose powder required during the calcination process. In addition, in some embodiments, the transition to YAG is complete in a single calcination cycle. Secondly, by using a transient sintering aid, such as introducing silicon dioxide into the original powder mixture, a Y-Al-Si-O liquid phase is formed during the calcination process. Due to the enhanced mass conversion by the liquid YA-Si-O sintering aid, this also causes the formation of YAG to be more easily carried out at a lower calcination temperature (and / or a shorter time or less calcination cycle). Thus, compaction according to the methods described herein is critical to the formation of YAG requiring fewer, if any, calcination cycle repetitions.
[0057] The spray-dried powder is compacted to reduce the distance between the powder particles, thereby enhancing the formation of YAG during the subsequent calcination process. Compacting the spray-dried powder to form a green compact may include compacting to a theoretical density of 35% or less. For example, compacting the spray-dried powder to form a green compact may include compacting to 20% theoretical density to 40% theoretical density, for example, 25% theoretical density to 40% theoretical density, 30% theoretical density to 40% theoretical density, or 35% theoretical density to 40% theoretical density. Compacting the spray-dried powder to form a green compact may include compacting to 20% or less theoretical density, 25% or less theoretical density, 30% or less theoretical density, 35% or less theoretical density, or 40% or less theoretical density. In a preferred embodiment, the amount of compaction is compacting to 35% theoretical density ± 10% or less. The density of the material compacted to a target of 35% theoretical density is 1.593 g / cm 3 ±10%.
[0058] Compacting the spray-dried powder can include uniaxial pressing or cold isostatic pressing. Hydramet devices can be used for compacting. The scope of the pressure for compacting can be 200psi to 2000psi, for example, 300psi to 1800psi, 400psi to 1600psi, 500psi to 1500psi or 1000psi to 1500psi. With regard to the lower limit, the pressure can be greater than 200psi, for example, greater than 300psi, greater than 400psi, greater than 500psi or greater than 1000psi. With regard to the upper limit, the pressure can be less than 2000psi, for example, less than 1800psi, less than 1600psi or less than 1500psi. In a preferred embodiment, the pressure is 500psi to 1500psi, for example, 1000psi to 1500psi.
[0059] In some embodiments, compaction includes forming the spray-dried powder (or particles) into a grinding media shape (0.75 inch diameter × 0.75 inch height) using a uniaxial press, such as a Hydramet uniaxial press. The spray-dried powder can be advantageously compacted in air at room temperature, although elevated temperatures are contemplated. Compacting can include cold pressing. The following are non-limiting example pressures that may be suitable for compacting spray-dried powders according to some embodiments of the present invention: Compacting the spray-dried powder can be performed at a pressure of 500 psi to 1500 psi, such as 500 psi to 1250 psi or 750 psi to 1000 psi.
[0060] Calcination
[0061] The method further includes the step of calcining the green compact in air to a theoretical density of 50% or less to form a YAG compact. In other words, calcination provides a step of converting the green compact into a YAG compact. 3 Al 5 O 12 Calcination achieves the desired phase while maintaining the discrete particles as a powder. In some embodiments, 3Y 2 O 3 :5Al 2 O 3 At least 95%, or at least 97%, or at least 98%, or at least 99% of 3 Al 5 O 12 In some embodiments, 100% 3Y 2 O 3 :5Al 2 O 3 Convert to Y 3 Al 5 O 12 Calcination further densifies the compact to a higher percentage of theoretical density relative to the green compact, while the YAG compact remains unsintered. In other words, the powder has not formed a dense solid.
[0062] For example, calcining the green compact to form the YAG compact may include compacting to a theoretical density of 50% or less. For example, calcining the green compact to form the YAG compact may include calcining to a theoretical density of 40% to 60% of theoretical density, for example, 45% to 60% of theoretical density, or 45% to 55% of theoretical density. Calcining the green compact to form the YAG compact may include calcining to a theoretical density of 40% or less, a theoretical density of 45% or less, a theoretical density of 50% or less, a theoretical density of 55% or less, or a theoretical density of 60% or less. In a preferred embodiment, the YAG compact is calcined to 50% theoretical density ±10% or less. The density of the YAG compact calcined to the 50% theoretical density target is 2.275 g / cm 3 ±10%.
[0063] Calcination may be carried out in any suitable furnace, such as an Armil furnace, at a temperature of 1100° C. to 1650° C. for 2 to 64 hours. Calcination may be carried out in air.
[0064] The temperature at which calcination is performed is from 1100°C to 1650°C. For example, calcination is performed at 1200°C to 1650°C, such as 1350°C to 1600°C, or 1450°C to 1550°C. In terms of the lower limit, calcination can be performed at a temperature above 1100°C, such as above 1200°C, above 1350°C, or above 1450°C. In terms of the upper limit, calcination can be performed at a temperature below 1650°C, such as below 1660°C or below 1550°C. In a preferred embodiment, calcination is performed at a temperature of 1450°C to 1550°C. Importantly, in some embodiments, calcination is performed at a temperature below the temperature generally considered to be sintering, which in some cases avoids sintering as described above. The disclosed method steps make lower temperature calcination possible, without which the calcination step would require a higher temperature and would encounter the troubles and damage associated therewith.
[0065] Calcination can be carried out at the above temperature for 2 hours to 64 hours. For example, calcination is carried out for 2 hours to 64 hours, for example, 4 hours to 48 hours, 6 hours to 24 hours, or 8 to 16 hours, or 10 to 14 hours. With regard to the lower limit, calcination can be carried out for a time greater than 2 hours, for example, greater than 4 hours, greater than 6 hours, greater than 8 hours or greater than 10 hours. With regard to the upper limit, calcination can be carried out for a time less than 64 hours, for example, less than 48 hours, less than 24 hours, less than 16 hours or less than 14 hours. In a preferred embodiment, calcination is carried out for 8 to 16 hours.
[0066] Calcination can be performed using a heat treatment scheme including one or more retentions in a single calcination cycle. Advantageously, two (or more) temperature graded calcinations provide a more complete transition to the desired YAG phase. Each retention is associated with a temperature and the time at that temperature. In some embodiments, calcination includes a heat treatment scheme with one retention, two retentions, three retentions, four retentions or more retentions. For example, calcination can include a first retention of a first temperature retention for a first time, a second retention of a second temperature retention for a second time, a third retention of an optional third temperature retention for a third time, and a fourth retention of an optional fourth temperature retention for a fourth time.
[0067] Therefore, calcination may include at least two holding temperatures. The at least two holding temperatures for calcination may be from 1100°C to 1650°C. For example, at least two holding temperatures are from 1200°C to 1650°C, such as from 1350°C to 1600°C, or from 1450°C to 1550°C. In terms of lower limits, at least two holding temperatures may be greater than 1100°C, such as greater than 1200°C, greater than 1350°C, or greater than 1450°C. In terms of upper limits, at least two holding temperatures may be lower than 1650°C, such as lower than 1660°C, or lower than 1550°C. In a preferred embodiment, at least two holding temperatures are from 1450°C to 1550°C. At least two holding temperatures may be the same or different.
[0068] The calcination comprising at least two holding temperatures can be carried out at the above-mentioned temperature, each time keeping 2 hours to 64 hours. For example, at least two holding times can be 2 hours to 64 hours, for example, 4 hours to 48 hours, 6 hours to 24 hours, or 8 hours to 16 hours, or 10 hours to 14 hours. With regard to the lower limit, at least two holding times can be greater than 2 hours, for example, greater than 4 hours, greater than 6 hours, greater than 8 hours or greater than 10 hours. With regard to the upper limit, at least two holding times can be less than 64 hours, for example, less than 48 hours, less than 24 hours, less than 16 hours or less than 14 hours. In a preferred embodiment, at least two holding times are 8 hours to 16 hours. At least two holding times can be identical or different.
[0069] In a preferred embodiment, the calcination comprises a first hold at a first temperature for a first time and a second hold at a second temperature for a second time, for example, the calcination comprises a first hold at a first temperature of 1450° C. to 1550° C. for a first time of 8 hours to 16 hours, and a second hold at a second temperature of 1450° C. to 1550° C. for a second time of 8 hours to 16 hours. In one embodiment, the calcination is performed in a single cycle at a first temperature of 1525° C. for 8 hours and then at a second temperature of 1550° C. for 8 hours. In a single cycle means continuously and without cooling between holds.
[0070] Importantly, calcination affects the transformation of the previously green compact into a yttrium aluminum garnet (YAG) compact, wherein the phase content can be determined by suitable techniques such as X-ray diffraction. 3 Al 5 O 12 , having a cubic crystal structure. The phase content of the YAG compact includes at least 90% by weight of Y 3 Al 5 O 12 , for example, at least 91 wt % of Y 3 Al 5 O12 , at least 92% by weight of Y 3 Al 5 O 12 , at least 93% by weight of Y 3 Al 5 O 12 , at least 94% by weight of Y 3 Al 5 O 12 , at least 95% by weight of Y 3 Al 5 O 12 , at least 96% by weight of Y 3 Al 5 O 12 , at least 97% by weight of Y 3 Al 5 O 12 , at least 98% by weight of Y 3 Al 5 O 12 or at least 99% by weight of Y 3 Al 5 O 12 .
[0071] After calcination, the phase content may advantageously include a small amount of secondary phase. The secondary phase may include silica, alumina, ceria (or other dopants), or a YAM or YAP phase indicating an incomplete phase transition to YAG. The phase content of the YAG compact includes up to 10% by weight of secondary phase, for example, up to 9% by weight of secondary phase, up to 8% by weight of secondary phase, up to 7% by weight of secondary phase, up to 6% by weight of secondary phase, up to 5% by weight of secondary phase, up to 4% by weight of secondary phase, up to 3% by weight of secondary phase, up to 2% by weight of secondary phase, up to 1% by weight of secondary phase. In some embodiments, a secondary phase that is zero or substantially zero is present and / or detectable.
[0072] Prior to calcination or included in the calcination heat treatment scheme may be an additional hold for binder burnout. This hold temperature is typically lower than the hold temperature for calcination that would affect the phase transition to YAG. As detailed above, binder burnout can be performed as part of the ramp up to the calcination temperature. The temperature range for binder burnout is 400°C to 600°C. For example, binder burnout is performed at 400°C to 600°C, for example, 425°C to 575°C, or 450°C to 550°C, or 475°C to 525°C. In terms of the lower limit, binder burnout may be performed at a temperature above 400°C, for example, above 425°C, above 450°C, or above 475°C. In terms of the upper limit, binder burnout may be performed at a temperature below 600°C, for example, below 575°C, below 550°C, or below 525°C. In a preferred embodiment, binder burnout is performed at a temperature of about 500°C ± 10%.
[0073] Optionally, the calcination can be repeated. In a preferred embodiment, only a single calcination is performed to provide a transition to YAG. In some embodiments, the calcination is repeated once, and in other embodiments twice. The method may include a total of one, two, or three calcinations. In some embodiments, the calcination is repeated at most once. The method does not require more than three calcinations. In embodiments of repeated calcinations, silica is added before each subsequent calcination. For repeated calcinations, the repeated cycles may include any or all of the following steps: adding silica, ball milling, spray drying, and compacting in each repeated cycle.
[0074] Secondary grinding (after calcination)
[0075] The method may further include the step of grinding the YAG compact and then drying the ground compact to produce YAG powder. The inventors have found that grinding can be performed without any added grinding media or grinding balls. Advantageously, grinding media is not required and is not added because the YAG compact material itself acts as a grinding medium, in other words, the grinding is autogenous. In some embodiments, the YAG compact includes a plurality of compacts, such as formed into a grinding medium shape (0.75 inch diameter × 0.75 inch height) using a uniaxial press in the above-mentioned cold pressing step. This step of autogenous grinding using the YAG compact is important because it ensures that impurities are not introduced during the grinding process. Therefore, the usual sources of additional contamination such as impurities from the grinding media are advantageously eliminated.
[0076] The grinding can be carried out in a polymer-lined grinding container. In some cases, for containers used in ball mills as described above, the dimensions of the container can be 15 cm to 60 cm in diameter and 15 cm to 60 cm in height. The grinding can be carried out in a non-reactive container, such as a polyurethane-lined grinding jar, for example, an Abbethane jar with a lift unit from Paul O'Abbe (Bensenville, IL), having dimensions: 30 cm diameter x 30 cm height. The contents of the polymer-lined grinding container include a YAG compact and a solvent. The container has no or substantially no added grinding media. Grinding the YAG compact includes causing the YAG compact material to self-crush on its own to produce a YAG powder. The solvent can be ethanol or isopropanol. The amount of solvent is in the range of 50 wt % to 80 wt % based on the total weight of the YAG solid component.
[0077] The grinding of YAG can be carried out at a speed of 15RPM to 70RPM. For example, the grinding speed can be 15RPM to 70RPM, for example, 30RPM to 70RPM, or 50RPM to 70RPM. Grinding can be carried out for 1 hour to 64 hours. For example, the grinding time can be carried out for 1 hour to 64 hours, for example, 4 hours to 48 hours, 8 hours to 24 hours or 12 hours to 20 hours. In some embodiments, grinding is carried out for 16 hours at 60RPM. In a preferred embodiment, the grinding of the YAG compact is carried out for at least 6 hours.
[0078] Grinding the YAG compact produces a powder having an average particle size distribution of less than 100 μm. In some embodiments, the average particle size distribution is less than 63 μm. This corresponds to a powder passing through a 230 mesh sieve. In other embodiments, the average particle size distribution is less than 44 μm. This corresponds to a powder passing through a 325 mesh sieve. The ground YAG compact material is sieved before drying to remove any agglomerates. In some embodiments, the YAG powder has a bimodal particle size distribution. The ground YAG compact is then dried to produce a YAG powder.
[0079] dry
[0080] Drying can be performed in a suitable dryer, such as a Fisher Scientific Lab drying oven at a temperature of 90° C. or less. In some embodiments, drying is performed at a temperature below 90° C. Drying can be performed for 2 hours to 24 hours.
[0081] The composition of the obtained YAG powder is Y 3 Al 5 O 12, and in some embodiments, the dopant concentration is 0.1 wt % to 3.0 wt %. During this process, the dopant concentration initially introduced is maintained at about ±10%. In some embodiments, the concentration of the dopant is constant throughout the process steps. In some aspects, the YAG powder may have up to 3 vol % oxides at the YAG grain boundaries as determined by X-ray diffraction (XRD) analysis. For example, the oxides may include aluminum oxide or ceria. In some embodiments, less than 1 vol % oxides are present at the YAG grain boundaries. Although the oxides present at the grain boundaries may make the YAG powder unsuitable for certain applications requiring transparency, such powders may be used in applications requiring translucency, or the presence of some oxides at the grain boundaries may be tolerable or even advantageous. For example, excess aluminum oxide at the YAG grain boundaries may result in increased thermal properties of the final product, such as increased thermal diffusivity. Using a superstoichiometric amount of aluminum oxide, such as 2.1 wt % Al 2 O 3 , the thermal diffusivity of YAG is significantly increased by 4% from 3.00mm 2 / s increased to 3.11mm 2 / s.
[0082] The YAG powder obtained according to the method herein can then be made into a final product, and the method may include sintering to obtain a dense product. Sintering by methods known in the art includes solid state sintering, hot pressing, hot isostatic pressing, etc. For sintering YAG, a temperature of 1500°C to 1800°C is required.
[0083] The temperature at which sintering is performed is generally higher than the calcination temperature of the method herein. For example, sintering is performed at 1500°C to 1800°C, for example, 1525°C to 1775°C, or 1550°C to 1750°C. In terms of lower limits, sintering can be performed at a temperature higher than 1500°C, for example, higher than 1525°C, higher than 1550°C, or higher than 1575°C. In terms of upper limits, sintering can be performed at a temperature lower than 1800°C, for example, lower than 1775°C, or lower than 1750°C.
[0084] Sintering can be carried out at the above-mentioned temperature for 2 hours to 64 hours. For example, sintering is carried out for 2 hours to 64 hours, for example, 4 hours to 48 hours, 6 hours to 24 hours, or 8 to 16 hours, or 10 to 14 hours. With regard to the lower limit, sintering can be carried out for a time greater than 2 hours, for example, greater than 4 hours, greater than 6 hours, greater than 8 hours or greater than 10 hours. With regard to the upper limit, sintering can be carried out for a time less than 64 hours, for example, less than 48 hours, less than 24 hours, less than 16 hours or less than 14 hours. In a preferred embodiment, sintering is carried out for 8 to 16 hours.
[0085] YAG structure and composition
[0086] The present disclosure relates to the synthesis of yttrium aluminum garnet (YAG) powder. YAG has a standard formula Y 3 Al 5 O 12 , which corresponds to a stoichiometric ratio of 3:5 for Y 2 O 3 (Yttrium Oxide) and Al 2 O 3 (Aluminum Oxide) or 3Y 2 O 3 :5Al 2 O 3 , or the ratio can be written as 0.6:1 Y 2 O 3 With Al 2 O 3 The YAG crystal structure is a complex cubic structure containing three different oxygen polyhedra, with Y in a ratio of 2:3. +3 The ions occupy the dodecahedral positions, Al 3+ The ions occupy octahedral and tetrahedral positions. This arrangement is due to the difference in ionic radius: The unit cell parameters can be changed from cubic symmetry by substitution with cations of different ionic radius. Cations with similar ionic radius can replace Y +3 , for example, by using Ce +3 Cationic substitution is performed to dope YAG. Cerium-doped YAG or Ce:YAG can be used as a phosphor in cathode ray tubes, white light emitting diodes, and scintillators. Other dopants are also contemplated. For example, the phosphor can be a transition metal or activated by a lanthanide.
[0087] Advantageously, in addition to being easily adaptable to the desired dopants, the YAG powder formed according to the method herein can also be easily sintered into a dense final product. For example, after a subsequent sintering process, the disclosed YAG powder is sintered at 1537° C. for 8 hours to form a product that can reach 98% of the theoretical density, while the commercially available YAG powder (Intematix G91, Fremont CA) can only reach 83% of the theoretical density when sintered at 1537° C. for 8 hours. In some embodiments, the sintered YAG product can have a theoretical density of 90% to 100%, for example, 92% to 100% of the theoretical density, or 94% to 99% of the theoretical density. Sintering to form a YAG product can include sintering to a theoretical density of 90% or greater, 92% or greater, 94% or greater, 96% or greater, or 97% or greater. In a preferred embodiment, the YAG compact is sintered to 98% theoretical density ±10% or less.
[0088] Doped YAG
[0089] The YAG powder synthesis as disclosed herein may also include the use of a dopant comprising a lanthanide or transition metal before converting the initial yttrium oxide and silica to YAG. Suitable dopants include lanthanide metals or transition metals ionized to +3. Suitable dopants may include those with an ionic radius equal to or less than 0.114 nm. The dopant is introduced into the process together with the initial yttrium oxide, silica and / or silica-rich yttrium oxide powder. The dopant may be enriched in the yttrium oxide powder or introduced as a separate powder to mix before preparing the powder slurry.
[0090] Lanthanides include chemical elements with atomic numbers from 57 to 71, characterized by having one valence electron in the 5d shell. Suitable lanthanides include lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium. Typically, a transition metal is an element whose atoms have a partially filled d subshell, or can produce cations with an incomplete d subshell. For purposes of this article, scandium and zinc are considered transition metals. Suitable transition metals include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium. The lanthanide or transition metal as a dopant herein may include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium or a combination thereof. In some embodiments, the dopant is scandium, zinc or cerium.
[0091] The dopant introduced during the synthesis of the YAG powder as disclosed herein may be in the form of a compound. The compound may be an oxide, a hydrate, a nitrate, a chloride, or a combination thereof. Example compounds for introducing cerium as a dopant include, but are not limited to: cerium dioxide (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 7H 2 O), cerium (III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O) or a combination thereof. Example compounds that introduce scandium as a dopant include, but are not limited to: scandium oxide (Sc 2 O 3 ) and scandium chloride hexahydrate (ScCl 3 6H 2 O). Example compounds that incorporate zinc as a dopant include, but are not limited to, zinc oxide (ZnO) and zinc chloride (ZnCl 2 ).
[0092] A more complete understanding of the components, methods, and apparatus disclosed herein may be obtained by referring to the accompanying drawings. These drawings are merely schematic representations based on convenience and ease of illustrating the present invention, and therefore, are not intended to indicate the relative size and dimensions of the device or its components and / or to define or limit the scope of the exemplary embodiments.
[0093] Figure 1 A flow chart of a method 100 according to an exemplary embodiment is shown. Step 110 is to introduce a raw powder. The raw powder may include yttrium oxide, silicon dioxide, and an optional dopant (or dopant compound). The powder (e.g., yttrium oxide rich in silicon dioxide) may be introduced or introduced as a separate powder (e.g., yttrium oxide and fumed silica) mixed to form a powder mixture. The powder mixture may be free of aluminum oxide, for example, aluminum oxide is not included in the powder mixture. Step 120 includes grinding the powder mixture. The ball milling in step 120 includes rolling a container containing the powder mixture of step 110 and a solvent and aluminum oxide grinding media. Due to the wear of the aluminum oxide grinding media during the grinding step 120 controlled by various parameters as described above, aluminum oxide is introduced into the powder slurry. After the desired amount of aluminum oxide is incorporated into the powder slurry, an optional organic binder is added, and a step 130 of spray drying the powder slurry is performed to produce discrete, uniformly distributed particles of aluminum oxide, yttrium oxide, silicon dioxide, and an optional dopant. The method 100 further includes a compacting step 140. The compacting is performed to achieve a theoretical density of 35% or less. This step is critical to shortening the distance between ions in the green compact. Therefore, during the next calcination step 150, it is easier to achieve a transition from the alumina, yttrium oxide and silica phases (and optional dopants) of the green compact to the YAG phase and form a YAG compact. The easier phase transition can be equivalent to at least one of the following: calcination can be performed at a lower temperature, for a shorter time and / or in fewer cycles compared to calcining loose material. The method 100 includes a grinding step 160 of the YAG compact in the absence of a grinding medium, allowing the YAG material to fall and crush itself to form ground YAG, which is then subjected to a drying step 170 and optional screening to produce a YAG powder.
[0094] In some embodiments, any or some of the steps or components disclosed herein may be considered optional. In some cases, any or some of the foregoing items in this specification may be explicitly excluded, for example, by claim language. For example, the language of the claims may be modified to state that the powder mixture does not contain or does not include a particular oxide or dopant.
[0095] As used herein, "greater than" and "less than" limitations may also include the numbers associated therewith. In other words, "greater than" and "less than" may be interpreted as "greater than or equal to" and "less than or equal to." It is contemplated that this language may be subsequently amended in a claim to include "or equal to." For example, "greater than 4.0" may be interpreted and subsequently amended in a claim to "greater than or equal to 4.0."
[0096] Example
[0097] Example 1
[0098] With 2.58 wt% CeO 2 Cerium-doped YAG (Ce:YAG) powder was synthesized with a dopant concentration of .
[0099] 71.33 g of yttrium oxide (99.9% purity, Y-104, Materion), 0.313 g of fumed silica (Sigma-Aldrich) and 3.225 g of cerium oxide (99.9% purity, C-1064, Materion) were introduced as batches into a 1.6 gal polyurethane-lined grinding jar of Abbethane (Paul O'Abbe) to form a powder mixture. 756.4 g of alumina grinding media (97.7% purity, about 13 mm in diameter and about 13 mm in height) and 300 ml of deionized water were also added to the grinding jar to form a powder slurry. The weight percentage of silica of Example 1 was 0.25 weight percent based on the total weight of the powder mixture. The powder slurry was then ball milled at 60 RPM for 16 hours.
[0100] After ball milling, the powder slurry was sieved using a polyethylene sieve (mesh #230) to separate the alumina grinding media and coarse particles from the powder slurry. The alumina grinding media was dried in a drying oven and the weight was measured again. The weight of the alumina grinding media after ball milling was 700.1 g, and the amount of alumina eroded from the grinding media was calculated to be 56.3 g. Figure 2 Graph 200 shows the amount of alumina eroded from the alumina grinding media during ball milling, wherein the amount of alumina eroded from the grinding media is shown as a function of the weight ratio of the alumina grinding media to the yttria charge. Without considering the amount of dopant and fumed silica, the yttria and alumina components of the powder slurry provide 3Y 2 O 3 :5Al 2 O 3 Stoichiometric YAG (71.33 g yttrium oxide and 53.67 g alumina) with an additional 2.63 g alumina. The molar ratio of yttrium oxide to alumina in the powder slurry (Y 2 O 3 :Al2 O 3 ) is calculated to be 3:5.25 (0.57:1).
[0101] The powder slurry further included 8 g of an acrylic polymer-based binder (B-60A, Rohm and Hass), which was stirred into the powder slurry using a magnetic bar and a magnetic stirrer for 30 minutes. The powder slurry was then spray dried using a Yamato DL410 spray dryer at an inlet temperature of 240° C., an outlet temperature of 90° C., and an air pressure of 0.1 MPa. The spray-dried powder slurry was passed through a 325 mesh polyethylene sieve to form a granular powder for compaction.
[0102] The granulated powder was then compacted into a green compact, which was formed into a grinding medium shape (0.75 inch diameter x 0.75 inch height) by a Hydramet uniaxial press. The density of the green compact was 1.49 g / cm 3 Or equivalent to 32.7% of the theoretical density of YAG.
[0103] The calcination was performed using the following heat treatment scheme: in a single cycle, heating to a temperature of 500°C and holding for 1 hour to remove the organic binder (binder burnout hold), increasing to a temperature of 1525°C and holding for 8 hours for calcination, and then increasing to a temperature of 1550°C and holding for 8 hours for further calcination. The density of the calcined compact was 2.21 g / cm 3 Or equivalent to 48.6% of the theoretical density of YAG. All debinding and calcination of the green compacts were carried out in an air atmosphere.
[0104] The calcined compact in 300 ml of ethanol was ground at 60 RPM for 6 hours and then sieved through a 230 mesh polyethylene sieve. The ground slurry was dried in an oven at 90° C. overnight (>12 hours). After drying, the YAG powder was passed through a 325 mesh polyethylene sieve.
[0105] Figure 3 The X-ray diffraction pattern of the resulting YAG powder of Example 1 is shown. Graph 300 shows that the major phase is YAG, with the peak represented by "Y". Minor phases detected as indicated by the less intense peaks include: Y 4 Al 2 O 9 (YAM), which has a peak represented by "M"; YAlO 3 (YAP), which has a peak represented by "P"; ceria, which has a peak represented by "C"; and alumina, which has a peak represented by "A". This advantageously has a high YAG content compared to YAG formed by conventional solid-state sintering methods. The YAG phase content is estimated to be about 92 wt% Y 3 Al 5O 12 .
[0106] To evaluate the sinterability of the synthesized YAG, the YAG powder was then mixed with 0.25 wt.% fumed silica and compacted by a uniaxial press, followed by sintering at 1500°C for 8 h in air to produce a sintered dense compact (e.g. Figure 4 shown).
[0107] Figure 4 is a scanning electron microscope (SEM) image 400 showing a 2.58 wt % CeO prepared in Example 1 after sintering at 1500° C. in air for 8 hours. 2 Typical microstructure of YAG powder with a dopant concentration of 1.5 wt %. The powder composition is stoichiometric YAG with an additional 2.13 wt % alumina (not including cerium oxide). The density of the sintered dense YAG ceramic was measured to be 4.41 g / cm 3 , which is equivalent to 97% of the theoretical density. As shown in the image 400, the sintered YAG 400 includes submicron spherical CeO at some grain boundaries. 2 YAG grains 410 of grains 420. Advantageously, no aluminum oxide grains are present in image 400.
[0108] Example 2
[0109] Undoped YAG (YAG) powder was synthesized. This batch included 71.33 g yttrium oxide (99.9%, Y-104, Materion) and 0.31 g fumed silica (Sigma-Aldrich) as in Example 1, but without the addition of CeO 2 The weight percentage of silicon dioxide in Example 2 was 0.25 wt % based on the total weight of the powder mixture. The powder was synthesized to obtain a 0.25 wt % superalumina YAG composition. The molar ratio of yttrium oxide to aluminum oxide in the powder slurry (Y 2 O 3 :Al 2 O 3 ) is calculated to be 3:5 (0.6:1). The heat treatment scheme of the green compact is as follows: heating to 500°C and holding for 1 hour to remove the organic binder, raising the temperature to 1525°C and holding for 8 hours for calcination, and then raising the temperature to 1550°C for further calcination for 8 hours. All heat treatments are carried out in air. The density of the calcined compact is about 50% of the theoretical density of YAG. The XRD pattern of Example 2 after heat treatment (not shown) is similar to Figure 3 Similar, but without CeO 2 The intermediate phases YAP and YAM were observed. Alumina was not detected as a minor phase.
[0110] The resulting powder of Example 2 was then calcined again by repeating the calcination heat treatment scheme for a second cycle: 1525°C for 8 hours, then raised to 1550°C for 8 hours. The density of the compact was not significantly affected by the second calcination cycle, and was approximately 50% of the theoretical density of YAG after the second calcination cycle.
[0111] Any and all intermediate phases (YAP and YAM) are then converted to pure YAG, such as Figure 5 , which shows the X-ray diffraction pattern of the resulting YAG powder after two calcination cycles of Example 2. Thus, the re-calcined Example 2 showed the presence of only the YAG phase (without a secondary phase), indicating a complete phase transformation to YAG.
[0112] Comparative Example A
[0113] Cerium-doped YAG (Ce:YAG) powders were prepared by in-situ sintering of a conventional commercial mixture of yttrium oxide and aluminum oxide powders with a dopant concentration of 3.0 wt% CeO 2 The composition of the powder is stoichiometric YAG with an additional 12 wt% alumina (not taking into account cerium oxide). Figure 6 6 is a SEM image 600, which shows the density of the YAG powder of Comparative Example A obtained by energy dispersive spectroscopy (EDS) analysis at various points after sintering at 1600° C. in air for 8 hours is 4.43 g / cm 3 , which is equivalent to 97% of the theoretical density. Importantly, this comparative sample requires a significantly higher sintering temperature to achieve the same density as Example 1. In addition, Comparative Example A includes a high content of alumina as a secondary phase, which is undesirable because it affects the purity and transparency properties of the YAG article. The secondary phases include alumina and ceria in amounts of approximately 12 wt % and 3 wt %, respectively.
[0114] EDS analysis results were collected at five locations, such as Figure 6 Table 1 summarizes the EDS results for Comparative Example A. Based on the EDS analysis, the phases of YAG 610, ceria 620, and alumina 630 were confirmed. Thus, Comparative Example A contains an alumina phase as a minor oxide phase, while Example 1 and (re-calcined) Example 2 do not.
[0115]
[0116]
[0117] *From carbon coating on coupons used for electronic discharge
[0118] **Calculated based on elemental composition
[0119] ***Anoxic Alumina
[0120] Examples 3 and 4, Comparative Examples B and C
[0121] In order to compare the effect of different calcination heat treatments (varying with temperature and / or time and / or number of cycles) on the phases produced, a scaled-up batch (375 g target) of the undoped powder prepared as in Example 2 was synthesized starting with 214 g of yttrium oxide and 0.938 g of fumed silica. As in Examples 1 and 2, the weight percentage of silica in the scaled-up batch was 0.25 wt %, based on the total weight of the powder mixture. Alumina was introduced similarly to Examples 1 and 2 by abrasion of the alumina grinding media during the grinding process. The powder was synthesized to obtain a stoichiometric YAG composition with 1.1 wt % excess alumina. The molar ratio of yttrium oxide to alumina in the powder slurry (Y 2 O 3 :Al 2 O 3 ) is calculated to be 3:5.13 (0.58:1).
[0122] Examples 3 and 4 and Comparative Examples B and C were formed into green compacts. The average density before and after calcination (at least five sample compacts for each example, and expressed as a percentage of theoretical density) is shown in Table 2.
[0123] All green compacts were heated to a temperature of 500° C. and maintained for 1 hour to burn out the binder, in other words, to remove the organic binder.
[0124] Then, Examples 3 and 4 as well as Comparative Examples B and C were calcined under different heat treatment conditions:
[0125] Example 3 Calcination cycle: In a single cycle, the temperature was raised to 1525°C and maintained for 8 hours for calcination in air, and then the temperature was raised to 1550°C for further calcination for 8 hours;
[0126] Comparative Example B Calcination cycle: Raise the temperature to 1475°C and keep in air for 8 hours for calcination;
[0127] Comparative Example C calcination cycle: heating to 1525°C and maintaining in air for 8 hours for calcination; and
[0128] Example 4: Compacts heat treated according to Comparative Example C (with calcination cycles as described above) were then calcined at 1550°C and held in air for 8 hours in an additional calcination cycle.
[0129] Compare the phases present in Example 3 and Example 4 and Comparative Examples B and Comparative Examples C as determined by X-ray diffraction analysis. Table 2 also includes data for Example 2, which was calcined again. Example 2, which was calcined again, underwent two cycles of calcination heat treatment, each cycle including 1525°C for 8h and 1550°C for 8h. The XRD data on the content of YAG and other phases (if present) are summarized in Table 2. Other phases may include, for example, YAP, YAM and alumina. The phases present in Example 3 were evaluated. The relative density after calcination heat treatment (the average value of at least five sample compacts for each example as a percentage of theoretical density) is also summarized in Table 2. The relative density is not applicable to Example 4, which has been synthesized in powder form.
[0130]
[0131]
[0132] **** Data from the X-ray diffraction pattern of re-calcined Example 2 as shown Figure 5 shown (two calcination cycles).
[0133] Calcination according to Example 2 provides the purest YAG powder (completely converted to Y 3 Al 5 O 12 , no secondary phase was detected), and included a first calcination cycle at 1525° C. for 8 hours and a second calcination cycle at 1550° C. for 8 hours. Example 4, which included a first calcination cycle at 1525° C. for 8 hours and a second calcination cycle at 1550° C. for 8 hours, also produced a calcined product having at least 94 wt % Y 3 Al 5 O 12 Calcination according to Example 3 at 1525°C / 8h+1550°C / 8h in a single calcination cycle produced a YAG phase having at least 92 wt.% 3 Al 5 O 12 Phase content of YAG high transformation.
[0134] Comparative Examples B and C show unacceptable amounts of non-YAG phase, indicating that the conversion to YAG is not yet complete. Comparative Example B shows only about 65 wt. % YAG. 3 Al 5 O 12 phase content, while Comparative Example C, which has a higher calcination temperature than Comparative Example B, shows only about 75 wt.% Y 3 Al 5 O 12 Phase content.
[0135] Implementation
[0136] The following embodiments are contemplated. All combinations of features and embodiments are contemplated.
[0137] Embodiment 1: A method for synthesizing yttrium aluminum garnet (YAG) powder, the method comprising: introducing yttrium oxide powder and silicon dioxide powder to form a powder mixture, wherein no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry; spray drying the powder slurry to form a spray-dried powder; compacting the spray-dried powder to a theoretical density of 35% or less to form a green compact, calcining the green compact in air to a theoretical density of 50% or less to form a YAG compact; and grinding the YAG compact without grinding media and then drying to produce YAG powder.
[0138] Embodiment 2: The method of any preceding or subsequent embodiment, wherein the mixed powder further comprises a dopant comprising a lanthanide or a transition metal.
[0139] Embodiment 3: The method according to any preceding or subsequent embodiment, wherein the lanthanide or transition metal is in the form of a compound, wherein the compound is an oxide, a hydrate, a nitrate, a chloride, or a combination thereof.
[0140] Embodiment 4: The method of any preceding or subsequent embodiment, wherein the lanthanide or transition metal is ionized to +3 and has an ionic radius equal to or less than 0.114 nm.
[0141] Embodiment 5: The method of any preceding or subsequent embodiment, wherein the lanthanide element or transition metal comprises scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or a combination thereof.
[0142] Embodiment 6: The method according to any preceding or subsequent embodiment, wherein the lanthanide or transition metal is scandium, zinc or cerium.
[0143] Embodiment 7: The method of any preceding or subsequent embodiment, wherein the dopant is present in an amount of 10 ppm to 6 wt % based on the total weight of the powder mixture.
[0144] Embodiment 8: The method of any preceding or subsequent embodiment, wherein the dopant is 0.1 wt% to 5 wt% ceria based on the total weight of the powder mixture.
[0145] Embodiment 9: The method of any preceding or subsequent embodiment, wherein the dopant is less than 3 wt% ceria based on the total weight of the powder mixture.
[0146] Embodiment 10: The method according to any preceding or subsequent embodiment, wherein the compound is cerium dioxide (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 7H 2 O) or cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O).
[0147] Embodiment 11: The method of any preceding or subsequent embodiment, wherein the yttrium oxide powder has a purity of 2N or higher.
[0148] Embodiment 12: The method of any preceding or subsequent embodiment, wherein the yttrium oxide powder has a purity of 3N or higher.
[0149] Embodiment 13: The method according to any preceding or subsequent embodiment, wherein the silicon dioxide content is 0.2 wt% to 0.3 wt% based on the total weight of the powder mixture.
[0150] Embodiment 14: The method of any preceding or subsequent embodiment, wherein the silica is fumed silica.
[0151] Embodiment 15: The method of any preceding or subsequent embodiment, wherein the aluminum oxide grinding media has 95.0% to 99.8% Al 2 O 3 purity.
[0152] Embodiment 16: The method of any preceding or subsequent embodiment, wherein ball milling the powder slurry comprises charging the powder mixture, solvent, and alumina grinding media into a ball milling container having a polymer liner.
[0153] Embodiment 17: The method according to any preceding or subsequent embodiment, wherein the solvent is distilled or deionized water.
[0154] Embodiment 18: The method of any preceding or subsequent embodiment, further comprising adding an organic binder to the powder slurry and mixing prior to spray drying the powder slurry.
[0155] Embodiment 19: The method of any preceding or subsequent embodiment, wherein the organic binder is water soluble.
[0156] Embodiment 20: The method of any preceding or subsequent embodiment, wherein the organic binder is present in an amount of 3 wt % to 9 wt % based on the total weight of the powder slurry.
[0157] Embodiment 21: The method of any preceding or subsequent embodiment, wherein the composition after ball milling comprises a stoichiometric amount of 3Y 2 O 3 :5Al 2 O 3 (0.6:1) and less than 3 wt% additional Al 2 O 3 .
[0158] Embodiment 22: The method of any preceding or subsequent embodiment, wherein the additional Al 2 O 3 Includes eroded portion of alumina grinding media.
[0159] Embodiment 23: The method according to any preceding or subsequent embodiment, wherein compacting the spray-dried powder comprises uniaxial pressing or cold isostatic pressing.
[0160] Embodiment 24: The method according to any preceding or subsequent embodiment, wherein compacting the spray-dried powder is performed at room temperature in air.
[0161] Embodiment 25: The method according to any preceding or subsequent embodiment, wherein compacting the spray-dried powder is performed at a pressure of 500 psi to 1250 psi.
[0162] Embodiment 26: The method according to any preceding or subsequent embodiment, wherein calcining is carried out at a temperature of 1100°C to 1650°C.
[0163] Embodiment 27: The method of any preceding or subsequent embodiment, wherein calcining is carried out at a temperature of 1450°C to 1550°C.
[0164] Embodiment 28: The method of any preceding or subsequent embodiment, wherein calcining is performed for 2 hours to 64 hours.
[0165] Embodiment 29: The method of any preceding or subsequent embodiment, wherein calcining is performed for 8 hours to 16 hours.
[0166] Embodiment 30: The method of any preceding or subsequent embodiment, wherein milling the YAG compact comprises placing the compact and the solvent into a milling container having a polymer liner.
[0167] Embodiment 31: The method according to any preceding or subsequent embodiment, wherein the solvent is ethanol or isopropanol.
[0168] Embodiment 32: The method of any preceding or subsequent embodiment, wherein grinding the YAG compact comprises grinding for at least 6 hours.
[0169] Embodiment 33: The method of any preceding or subsequent embodiment, wherein grinding the YAG compact comprises comminuting the YAG compact material against itself to produce a YAG powder having an average particle size distribution of less than 100 μm.
[0170] Embodiment 34: The method of any preceding or subsequent embodiment, wherein the average particle size distribution is less than 63 μm.
[0171] Embodiment 35: The method according to any preceding or subsequent embodiment, wherein the average particle size distribution is less than 44 μm.
[0172] Embodiment 36: The method of any preceding or subsequent embodiment, wherein the ground YAG compact material is sieved prior to drying.
[0173] Embodiment 37: The method of any preceding or subsequent embodiment, wherein the YAG powder has a bimodal particle size distribution.
[0174] Embodiment 38: The method according to any preceding or following embodiment, wherein drying is carried out at a temperature below 90°C.
[0175] Embodiment 39: A method for synthesizing doped yttrium aluminum garnet (YAG) powder, the method comprising: providing yttrium oxide powder, silica powder and at least one dopant powder formed by an oxide, hydrate, nitrate or chloride of a lanthanide element or a transition metal and mixing them to form a powder mixture, wherein no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry; adding an organic binder to the powder slurry and mixing to form a sprayable powder slurry; spray drying the sprayable powder slurry to form a spray-dried powder; compacting the spray-dried powder to a theoretical density of 35% or less to form a green compact, calcining the green compact in air to a theoretical density of 50% or less to form a YAG compact; and grinding the YAG compact without grinding media and then drying to produce a doped YAG powder.
[0176] Embodiment 40: A yttrium aluminum garnet (YAG) composition comprising: Y 3 Al 5 O 12 ; and less than 3 wt% additional Al 2 O 3 , where the additional Al 2 O 3 Includes eroded portion of alumina grinding media.
[0177] Embodiment 41: The composition of any preceding or subsequent embodiment, further comprising a dopant concentration of at least 1 at %.
[0178] Embodiment 42: A phosphor wheel or LED lighting device comprising the composition of any of the preceding aspects.
[0179] Although specific terms are used in the following description for the sake of clarity, these terms are intended only to refer to the specific structures selected for the embodiments illustrated in the accompanying drawings, and are not intended to define or limit the scope of the present invention. In the accompanying drawings and the following description, it should be understood that similar reference numerals refer to components with similar functions.
[0180] The singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise.
[0181] As used in the specification and claims, the term "comprising" may include the embodiments "consisting of" and "consisting essentially of." As used herein, the terms "comprising," "including," "having," "having," "may," "containing," and variations thereof are intended to be open-ended, transitional phrases, terms, or words that require the presence of specified ingredients / components / steps and allow for the presence of other ingredients / components / steps. However, such descriptions should be construed as also describing a composition, article, or process as "consisting of" and "consisting essentially of" the listed ingredients / components / steps, which allows for the presence of only the specified ingredients / components / steps except for any impurities that may result therefrom, and excludes other ingredients / components / steps.
[0182] Numerical values in the specification and claims of this application should be understood to include values that are the same when reduced to the same number of significant figures, and values that differ from the specified value by less than the experimental error of the type of routine measurement techniques described in this application used to determine the value.
[0183] All ranges disclosed herein are inclusive of the recited endpoints and are independently combinable (eg, a range of "2 grams to 10 grams" includes the endpoints 2 grams or 10 grams and all intermediate values).
[0184] When a material is described as having an average particle size or an average particle size distribution, it is defined as the particle size at which the cumulative percentage reaches 50% (by volume) of the total number of particles. In other words, 50% of the particles have a diameter above the average particle size, and 50% of the particles have a diameter below the average particle size. The size distribution of particles will be Gaussian, with the upper and lower quartiles being 25% and 75% of the specified average particle size, respectively, and all particles being less than 150% of the specified average particle size.
[0185] The process steps described herein refer to temperature, and unless otherwise specified, this refers to the temperature reached by the referenced material, not the temperature of the set heat source (e.g., furnace, oven). The term "room temperature" refers to the range of 20°C to 25°C (68°F to 77°F).
[0186] The term "about" can be used to include any numerical value that can vary without changing the basic function of the value. When used with a range, "about" also discloses the range defined by the absolute values of the two endpoints, for example, "about 2 to about 4" also discloses a range of "2 to 4". The term "about" can refer to plus or minus 10% of the specified number.
[0187] Although the present invention has been described in detail, it will be apparent to those skilled in the art that modifications are made within the spirit and scope of the present invention. In view of the foregoing discussion, the relevant knowledge and references in the art discussed above related to the background technology and specific embodiments, the entire disclosure of which is incorporated herein by reference. In addition, it should be understood that the various aspects of the present invention and the various embodiments and the parts of the various features described below and / or in the appended claims may be combined or interchanged in whole or in part. In the foregoing description of the various embodiments, as will be understood by those skilled in the art, those embodiments that reference another embodiment may be appropriately combined with other embodiments. In addition, it will be understood by those of ordinary skill in the art that the foregoing description is exemplary only and is not intended to be limiting.
Claims
1. A method for synthesizing yttrium aluminum garnet powder, the method comprising: introducing yttria powder and silicon dioxide powder to form a powder mixture, wherein no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media as the sole source of alumina and a solvent to form a powder slurry; processing the powder slurry into a green compact; The green compact is calcined in air at a temperature of 1100° C. to 1650° C. for 8 hours or more to a theoretical density of 50% or less to form a composite having at least 92 wt.% Y3Al5O 12 Yttrium aluminum garnet compact; as well as The yttrium aluminum garnet compact is ground without grinding media and then dried to produce the yttrium aluminum garnet powder.
2. The method of claim 1, wherein the processing comprises spray drying the powder slurry to form a spray-dried powder, and compacting the spray-dried powder to a theoretical density of 35% or less to form a green compact.
3. The method according to claim 1, wherein the calcination is performed at a temperature of 1450°C to 1550°C for 8 hours to 16 hours.
4. The method of claim 1, further comprising sintering the yttrium aluminum garnet powder to greater than 96% theoretical density.
5. The method of claim 1 wherein the alumina grinding media has a purity of 95.0% to 99.8% Al2O3 and wherein the composition after ball milling comprises a stoichiometric 3Y2O3:5Al2O3 and less than 3 wt% additional Al2O3.
6. The method of claim 5, wherein the additional Al2O3 comprises an eroded portion of the aluminum oxide grinding media.
7. The method of claim 1, wherein grinding the yttrium aluminum garnet compact comprises causing the yttrium aluminum garnet compact material to pulverize against itself to produce a yttrium aluminum garnet powder having an average particle size distribution of less than 100 μm.
8. The method of claim 1, wherein introducing the powder further comprises a dopant, wherein the dopant comprises a lanthanide or a transition metal, wherein the lanthanide or transition metal is in the form of a compound, wherein the compound is an oxide, a hydrate, a nitrate, a chloride, or a combination thereof.
9. The method according to claim 8, wherein the lanthanide element or transition metal is ionized to a valence of +3 and has an ion radius equal to or less than 0.114 nm.
10. The method of claim 8, wherein the lanthanide element or transition metal comprises scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or a combination thereof.
11. The method according to claim 8, wherein the content of the dopant is 10 ppm to 6 wt% based on the total weight of the powder mixture.
12. The method of claim 11, wherein the dopant is less than 3 wt% ceria based on the total weight of the powder mixture.
13. The method according to claim 1, wherein the yttrium oxide powder has a purity of 2N or higher, and wherein the content of the silicon dioxide is 0.1 wt% to 0.3 wt% based on the total weight of the powder mixture.
14. The method of claim 1, wherein introducing the powder further comprises a dopant, wherein the dopant comprises a lanthanide or a transition metal, wherein the lanthanide or the transition metal is in the form of a compound, wherein the compound is cerium dioxide (CeO2), cerium (III) chloride heptahydrate (CeCl3·7H2O) or cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O).
15. The method of claim 8, wherein the lanthanide element or transition metal is scandium, zinc or cerium.
16. The method of claim 8, wherein the dopant is 0.1 to 5 wt% ceria based on the total weight of the powder mixture.
17. The method according to claim 13, wherein the yttrium oxide powder has a purity of 3N or higher.
18. The method of claim 1, wherein the alumina grinding media has an attrition of 5 wt% to 10 wt%.
19. A method for synthesizing doped yttrium aluminum garnet powder, the method comprising: introducing and mixing yttrium oxide powder, silicon dioxide powder and at least one dopant powder formed from an oxide, hydrate, nitrate or chloride of a lanthanide element or a transition metal to form a powder mixture, wherein no aluminum oxide is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media as the sole source of alumina and a solvent to form a powder slurry; processing the powder slurry into a green compact; The green compact is calcined in air at a temperature of 1100° C. to 1650° C. for 8 hours or more to a theoretical density of 50% or less to form a composite having at least 92 wt.% Y3Al5O 12 Yttrium aluminum garnet compact; as well as The yttrium aluminum garnet compact is ground without grinding media and then dried to produce the doped yttrium aluminum garnet powder.